Câu 1:
\(\left\{{}\begin{matrix}m^2x+y=3m\\-4x-y=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}m^2x-4x=3m+6\\-4x-y=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\left(m^2-4\right)=3m+6\\-4x-y=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=\dfrac{3m+6}{m^2-4}=\dfrac{3}{m-2}\\y=6-\dfrac{3}{m-2}=\dfrac{6m-15}{m-2}\end{matrix}\right.\)Câu 2:
\(\left\{{}\begin{matrix}5x-y=13\\x+3y=-7\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}15x-3y=39\\x+3y=-7\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}16x=32\\x+3y=-7\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=2\\y=-3\end{matrix}\right.\)
Anh vẫn thấy bình thường mà em, vẫn thấy cách làm